The macrodynamics of Indian Rupee swap yields - Tanweer Akram; Khawaja Abdullah al Mamun (Levy Economics Institute of Bard College, 2023)
This paper econometrically models the dynamics of Indian rupee (INR) swap yields based on key macroeconomic factors using the autoregressive distributive lag (ARDL) approach. It examines whether the short-term interest rate has a decisive influence on long-term INR swap yields after controlling for other factors, such as core inflation, the growth of industrial production, the logarithm of the equity price index, and the logarithm of the INR exchange rate. The estimated models show that the short-term interest rate has an important influence on the swap yields. This implies that the Reserve Bank of India (RBI) can sway borrowing and lending rates not just on Indian government bonds but also INR-denominated private-market financial instruments, such as swaps and swaptions.
Keywords: E43; E50; E58; E60; G10; G12; 330; Interest Rate Swaps; Swap Yields; Inflation; Reserve Bank of India; India